Interface design features of mobile application for senior citizens - Natrah Abdullah; Nur Farahin binti Abdul Hamid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Reading Al-Quran is one of spiritual activities and as for Muslims, and they believed God would reward those who read and practice it. In order to dedicate remaining years of their life to God and to bring peace of mind, most of the senior citizens are spending their time doing spiritual activities such as reciting Al-Quran. With the advancement of technology, the sources of Al-Quran are also changing. There are many Al-Quran application being developed in the market and can be download and install easily in mobile devices such as smartphone. However, the application that have been developed often ignored needs and limitation of senior users, that causing them to feel unease to use the mobile application. Hence, the purpose of this study is to investigate the user interface design principles of mobile Al-Quran application for senior citizens. For this purpose, the study has conducted a literature review, interview session usability study, the user interface design principles were identified. Using the principles, this study proposed a mobile application and an observation has been conducted with the senior citizens as a validation of the principles. Validation is based on usability evaluation on effectiveness, efficiency and satisfaction. The results show that the application is satisfactory and usable for the users. In future, the same research interest researcher can explore the audio and navigating in the interface by audio commands. The prototype could be extended to meet the needs of senior citizens that having the problem such as Parkinson and Alzheimer disease.